Perceptions on the Relationship between Public Relations Practitioners and Journalists - Kiranjit Kaur; Halimahton Shaari (Kajian Malaysia, 2006)
This research examines perceptions on the relationship between public relations practitioners and journalists based on four categories of relationship: Satisfaction with contributions made to each other, interdependence, trust and ethical practices. A survey of 48 public relations practitioners and 63 journalists was conducted regarding their perceptions on each other’s profession. Public relations practitioners polled for this survey were from the various government and corporate organisations while the journalists were from the print and electronic media organisations and publishing houses. Generally, the surveyindicates some differences and similarities in the perceptions of the two groups with public relations practitioners holding stronger perceptions than the journalists on the various aspects of their relationship. The data suggests that public relations practitioners believe more strongly that the information they provide to the journalists enables the latter to perform more satisfactorily compared to the journalists who think less strongly of the contribution made by the former. The public relations practitioners also seem to think that there is more of a symbiotic relationship between the two groups than the journalists.